2022
DOI: 10.3390/ma15155257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alumina on Crystallization Behavior of Calcium Ferrite in Fe2O3-CaO-SiO2-Al2O3 System

Abstract: Al2O3 is a gangue component in iron ores, significantly influencing the formation and crystallization of calcium ferrite in the sintering process. But the mechanism of the Al2O3 effect on the crystallization of calcium ferrite is rarely reported. In this work, a crystallization device was designed to investigate the crystallization behavior of calcium ferrite in Fe2O3-CaO-SiO2-Al2O3 melt under non-isothermal conditions. XRD, SEM-EDS, and optical microscopy were used to identify the crystalline phase and the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…An increase in the Al 2 O 3 mass% from 1.5 to about 2.0 resulted in more liquid phase generation and higher liquid phase viscosity [29][30][31]. The rise in the liquid phase led to the formation of smaller magnetite crystal particles.…”
Section: Model Significance Analysismentioning
confidence: 99%
“…An increase in the Al 2 O 3 mass% from 1.5 to about 2.0 resulted in more liquid phase generation and higher liquid phase viscosity [29][30][31]. The rise in the liquid phase led to the formation of smaller magnetite crystal particles.…”
Section: Model Significance Analysismentioning
confidence: 99%
“…In particular, the papers focus on the description of the different phases of SFCA-I and the study of their phase and chemical composition, crystalline structures, and formation conditions. In the works of Chinese scientists [24,25], correlations were found between the phase components of the agglomerate and their prop-erties based on the composition and characteristics of the concentrate. Mumme W.G.…”
Section: Introductionmentioning
confidence: 99%
“…Bonding phase is the premise for the consolidation of sintered raw materials into blocks. It binds the unmelted sinter together and determines the strength and yield of sinter [4,6]. A large number of studies have shown that in the bonding phase of sinter, calcium ferrite, especially Silico-Ferrite of Calcium and Aluminum is the best, which is usually abbreviated as SFCA.…”
Section: Introductionmentioning
confidence: 99%